Uji Antibakteri Kombinasi Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L) Dan Daun Kersen (Muntingia calabura L) Terhadap Staphylococcus aureus - Oktariani Pramiastuti; Desi Sri Rejeki; Inul Maghfiroh (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Infectious diseases are one of the main causes of diseases in tropical regions like Indonesia. Infectious diseases usually can be cured by antibiotics, since the use of antibiotics has side effects and long-term resistance and prices that are not affordable, it needs a role of herbs that can weaken the activity of these bacteria. Kersen plants contains various chemical compounds namely flavonoid compounds, saponins, and tannins that have antioxidant potential and antibacterial activity. Belimbing wuluh contains flavonoid compounds. This research was conducted to find out the antibacterial activity of extract combination of kersen leaf (Muntingia calabura L) and belimbing wuluh leaf (Averrhoa bilimbi L) against Staphylococcus aureus. Extract of Kersen leaf and Belimbing wuluh leaf were obtained by maceration method using ethanol 96% for 5 days. The antibacterial activity test was performed by diffusion method using disc paper based on the inhibit zone diameter or clear zone formed around the disc paper. The test was conducted by extract comparison of kersen leaf and belimbing wuluh leaf at 30% concentration namely 1:1, 1:2, 2:1, 1:3 and 3:1 against Staphylococcus aureus. The results showed that the extract comparison of kersen leaf and belimbing wuluh leaf 1:1 had a weak inhibitory power because of its inhibitory value ≤ 5 mm, that was 4.67 mm. While the ratio of 1:2, 2:1, 1:3 and 3:1 had a moderate inhibition resistance value ranges from 5-10 mm; 6.33 mm,7.16 mm, 7.67 mm, and 7.83 mm. Extract rendemen of kersen leaf was 11.94% and belimbing wuluh leaf was 6.28%.